Injuries in national Olympic level judo athletes: an epidemiological study - Kim, K.-S.; Park, K. J.; Lee, J.; Kang, B. Y. (British Journal of Sports Medicine, 2015)
Purpose: To present an epidemiological study of injuries found among South Korea's National level Judo athletes as a foundation for future injury prevention and skill enhancement in this group. Methods: This study is a prospective study on a 4-year injury assessment held from January 2010 to December 2013 at the training centre in South Korea for National Level athletes. Athlete's weight class, gender, injury location and injury grade (grade I=1-3 treatment days, grade II=4-7 treatment days, and grade III =8 treatment days) were analysed. Results: There were a total of 782 injuries recorded during this period, equalling to four injuries per athlete annually. Almost half of these injuries (47%) were grade I injuries. Injury occurrence was the highest in the Lower body (44.2%). This was then followed by injuries in the upper body (29.8%), trunk (20.3%) and head and neck (5.6%). Men and women showed similar, non-significantly different trends in the proportion of body parts injured. Women experienced more grade III injuries than males (p=0.0228). Comparison between women in different weight classes also showed that heavyweights incurred more grade III injuries than lightweights (p=0.0087). Lightweights had a higher rate of injury than heavyweights in males and females, although this was statistically significant only among males (p<0.001). Conclusions: Many body regions are prone to injury in the elite judo population. Women, especially those in the heavyweight classification, were more prone to severe injuries. Lightweights experienced more injuries than heavyweights among male athletes. Specifically, further studies are needed to confirm these findings and to address the impact of rapid weight loss practices on injury risk to implement effective preventive measures.